2013
DOI: 10.1371/journal.pone.0063847
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TNF in the Brain Reverses Alterations in RAS Components and Attenuates Angiotensin II-Induced Hypertension

Abstract: Dysfunction of brain renin-angiotensin system (RAS) components is implicated in the development of hypertension. We previously showed that angiotensin (Ang) II-induced hypertension is mediated by increased production of proinflammatory cytokines (PIC), including tumor necrosis factor (TNF), in brain cardiovascular regulatory centers such as the paraventricular nucleus (PVN). Presently, we tested the hypothesis that central TNF blockade prevents dysregulation of brain RAS components and attenuates Ang II-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 38 publications
(62 reference statements)
8
86
1
4
Order By: Relevance
“…Increased proinflammatory cytokines expression in autonomic control areas, as the PVN, has been identified as a major central molecular mechanism to decrease baroreflex function, to reduce HR variability, and to increase pressure variability and renal sympathetic nerve activity, thus contributing to the development/maintenance of hypertension (7,13,18,38,39). It was also shown that hypertensive rats exhibit elevated proinflammatory cytokines TNF-␣ and IL-6 expression in the PVN (2,31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased proinflammatory cytokines expression in autonomic control areas, as the PVN, has been identified as a major central molecular mechanism to decrease baroreflex function, to reduce HR variability, and to increase pressure variability and renal sympathetic nerve activity, thus contributing to the development/maintenance of hypertension (7,13,18,38,39). It was also shown that hypertensive rats exhibit elevated proinflammatory cytokines TNF-␣ and IL-6 expression in the PVN (2,31).…”
Section: Discussionmentioning
confidence: 99%
“…PVN was isolated from frozen brain sections using a Stoelting brain punch (Stoelting) and, then, the tissue was homogenized with RIPA lysis buffer, as previously described (2,7,18,39). The protein concentration was measured using a bicinchoninic acid (BCA) protein assay kit (Pierce).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NOX-2 and NOX-4 mRNA expression was determined by real-time RT-PCR as previously described [18,23]. The primer sequences used were as follows: NOX-2 forward 5 0 -CTGCCAGTGTGTCGGAATCT-3 0 ; NOX-2 reverse 5 0 -TGTGAATGGCCGTGTGAAGT-3 0 ; NOX-4 forward 5 0 -GGATCACAGAAGGTCCCTAGC-3 0 ; NOX-4 reverse 5 0 -AGAAGTTCAGGGCGTTCACC-3 0 ; GAPDH forward 5 0 -AGACAGCCGCATCTTCTTGT-3 0 ; and GAPDH reverse 5 0 -CTTGCCGTGGGTAGAGTCAT-3 0 .…”
Section: Real-time Pcrmentioning
confidence: 99%
“…Therefore, there is the possibility that the loss of the anticontractile effect of PVAT in hypertension could be due to a release of TNF-α, which then exerts a procontractile effect by a mechanism involving generation of reactive oxygen species and angiotensin II [62,66]. The observations that treatment with TNF-α antagonist reduced angiotensin-induced hypertension [67,68] and that chronic blockade of angiotensin AT 1 receptor significantly reduced circulating levels of TNF-α [69] are consistent with the existence of cross-talk between angiotensin II and TNF-α (fig. 3).…”
Section: Infiltration Of Macrophages As a Possible Reason For The Losmentioning
confidence: 99%